EFEKTIVITAS SIMULASI PhET DENGAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SISWA SMP PADA MATERI LISTRIK DINAMIS - Ach Taufik Dwi Wardani; Laily Rosdiana (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This research aimed to describe three important things in learning, namely implementation of learning, student process skills, and student response after participating in learning with guided inquiry methods using PhET on dynamic electrical materials. This research method uses pre-experimental with one group pretest and posttest design with research subjects are 14 students of class IX-B Jati Agung Waru Junior High School. Data obtained by observation, tests, and questionnaires method are then analyzed in quantitative descriptions. The resultssshowed that the percentage of learning effectiveness of 96.22 during 2 meetings was said to be an excellent and very practical category that was getting more than 90%. Science process skills gained a total N-Gain of 0.82 which is high in category and effectively having increased. Students responded by 90.15 is categorized as excellent response. Basedoon theedescription above, ittcan beeconcluded that learning with guided inquiry methods that using PhET can improve the skills of science processes in dynamic electrical materials.